Hey,
<br><br>I am new with Haskell so I think this will be a pretty dumb 
question.
<br>I would like to make a function that makes this:
<br><br>listbool :: [[Int]] -&gt; [[Bool]]
<br><br>in this way:
<br>listbool [[1,2],[3,4]] == [[True, True],[False, False]]
<br>listbool [[1],[5,5],[5,4],[2]] == [[True],[False, False],[True, 
True], [False]]
<br><br>So always True from the elements of the first list, False from 
the elements of the second one, etc...
<br><br><br>Can you help me to do that?
<br>Thanks for your help!<br><br>Maur Toter<br>